2018
DOI: 10.3390/app8091549
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Analysis of Water Based (Cu–Al2O3) Hybrid Nanofluid in an Asymmetric Channel with Dilating/Squeezing Walls Considering Different Shapes of Nanoparticles

Abstract: An innovative concept of water-based Cu–Al2O3 hybrid nanofluid has been employed to investigate the behavior of flow and heat transfer inside a rectangular channel whose permeable walls experiences dilation or contraction in height. The transformed set of ordinary differential equations is then solved by a well-known Runge–Kutta–Fehlberg algorithm. The analysis also includes three different shapes of copper nanocomposites, namely, platelet, cylinder and brick- shaped. The impact of various embedded parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…The reduced nonlinear ODEs are solved numerically by shooting method with Runge‐Kutta fourth‐order scheme. The outcomes are analyzed for nondimensional velocity components, temperature, concentration, entropy generation, and Bejan number with respect to various fluid and geometric parameters and presented in the form of graphs and table and from these, we concluded that The temperature profile of the fluid is enhanced with the radiation parameter, whereas the concentration decreases with the Eckert number. The Soret and Dufour parameters exhibit a similar trend for heat and mass transfer characteristics of Casson fluid. The Bejan number of the fluid is raised with a radiation parameter, whereas the entropy is decreased with the Casson fluid parameter. The temperature and concentration profiles of the fluid decrease with the squeezing Reynolds number. The effects on Bejan number for the Schmidt number and Dufour number are an opposite trend. The Schmidt and Dufour numbers exhibit the opposite trend for Bejan number The profiles of velocity components are similar for Casson fluid parameter and squeezing Reynolds number The current results show good agreement with the published work for a viscous fluid.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The reduced nonlinear ODEs are solved numerically by shooting method with Runge‐Kutta fourth‐order scheme. The outcomes are analyzed for nondimensional velocity components, temperature, concentration, entropy generation, and Bejan number with respect to various fluid and geometric parameters and presented in the form of graphs and table and from these, we concluded that The temperature profile of the fluid is enhanced with the radiation parameter, whereas the concentration decreases with the Eckert number. The Soret and Dufour parameters exhibit a similar trend for heat and mass transfer characteristics of Casson fluid. The Bejan number of the fluid is raised with a radiation parameter, whereas the entropy is decreased with the Casson fluid parameter. The temperature and concentration profiles of the fluid decrease with the squeezing Reynolds number. The effects on Bejan number for the Schmidt number and Dufour number are an opposite trend. The Schmidt and Dufour numbers exhibit the opposite trend for Bejan number The profiles of velocity components are similar for Casson fluid parameter and squeezing Reynolds number The current results show good agreement with the published work for a viscous fluid.…”
Section: Discussionmentioning
confidence: 90%
“…From the figure, it is observed that as Du increases the temperature and concentration follow the same trend of Sc , whereas entropy generation number, Bejan number follows the opposite trend. Table represents the numerical outcomes of the coefficient of skin friction and Nusselt number at the upper plate for the viscous case and compared with existing results …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gupta and Gupta identified that the unsteady squeezing channel flow problem could be simplified to the remarkable extent through similarity transformation in the case that the parallel plates are kept at a distance, which varies as the square root of a linear function of time. The unsteady squeezing flow problems were investigated by several researchers, eg, Verma, Singh et al, Hamza, Duwairi et al, Mustafa et al, Umar Khan and coworkers, Khan et al, Mohyud‐Din et al, Adnan et al, Adesanya et al, Saba et al, Khan et al, and Sultan et al with consideration of various physical properties and computational techniques.…”
Section: Introductionmentioning
confidence: 99%